Inclusion of Cistus ladanifer in ruminant diets : an approach to improve the nutritional value of edible fats - Guerreiro, Olinda Rosa Fragoso das Neves (2018)
Tese de Doutoramento em Ciências Veterinárias, na especialidade de Produção Animal